VASECTOMY IN ISLAMIC LAW PERSPECTIVE - Lubis, Said Ahmad Sarhan (Inspiring Law Journal, 2025)
This writing discusses the Islamic perspective on one of the permanent contraceptive of Family Planning (KB), namely Vasectomy. Vasectomy is term of surgery science which is formed from two words namely vas and entomic. Vas or vase differentia means seed channel namely the channel circulates spermatozoa out of testis where the seed cell is produced towards pocket of sperm (vesikulamenalis) as place of spermatozoa reception before being spread while having ejaculation. Ektomi or ektomia means cutting of part. So vasectomy means cutting of part (0,5-1 cm) of seed channel so there is distance between the edge of seed channel of testis side, other seed channels left and each of both of the remaining channel edge are tied then it is clogged. Indonesia Cleric Assembly (MUI) as institution of discussion for all Indonesian clerics has legalized a fatwa about prohibition of vasectomy. The people who have done the practice of vasectomy just think to avoid bearing children anymore in order to reduce economy problem